1980
DOI: 10.1159/000275478
|View full text |Cite
|
Sign up to set email alerts
|

Apical Lesions of the Cochlea in Idiopathic Endolymphatic Hydrops and other Disorders: Pathophysiological Implications

Abstract: Apical lesions of the cochlea may be caused by direct trauma, impairment of blood supply, contamination of perilymphatic fluid and endolymphatic hydrops. It is proposed that endolymphatic hydrops causes apical lesions when endolymph or its components leak into the perilymphatic fluid and pass through the helicotrema to degrade the tissue fluid environment of the sensory and neural structures in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…low-frequency hearing loss), primarily manifest in the cochlear apex. These pathological abnormalities were attributed to chronic alterations in the local fluid environment of the cochlear apex [ 82 ]. Ménière's disease-specific abnormalities in the cochlear apex that explain these morphological and functional impairments have not yet been described at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…low-frequency hearing loss), primarily manifest in the cochlear apex. These pathological abnormalities were attributed to chronic alterations in the local fluid environment of the cochlear apex [ 82 ]. Ménière's disease-specific abnormalities in the cochlear apex that explain these morphological and functional impairments have not yet been described at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperosmolar fluid reflux theory: A somewhat similar theory to the electrolyte imbalance theory, Schucknecht77 along with Levenson17 and Okamoto74 theorize that the endolymphatic sac fluid, which is known to contain hyperosmolar fluid, can reflux more easily through the enlarged endolymphatic sac and duct and enter the inner ear resulting in damage to the inner ear structures. Arguing against this theory is an MRI study that found endolymphatic sac volume and intensity vary dynamically and independently of hearing in cases of enlarged vestibular aqueduct.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated toxic insults could account for fluctuations in threshold and word discrimination, eventually producing ganglion cell loss in the apical tum. 64 Continued viral release may eventually extend down the scala tympani to affect more basal segments of the SG, producing an even threshold elevation for all frequencies in advanced MD.…”
Section: Discussionmentioning
confidence: 99%